Towards 4D printing in pharmaceutics - Gazzaniga, Andrea; Foppoli, Anastasia; Cerea, Matteo; Palugan, Luca; Cirilli, Micol; Moutaharrik, Saliha; Melocchi, Alice; Maroni, Alessandra (International journal of pharmaceutics: X, 2023)
Four-dimensional printing (4DP) is emerging as an innovative research topic. It involves the use of smart materials for three-dimensional printing (3DP) of items that change their shape after production, in a programmed way over time, when exposed to appropriate external non-mechanical stimuli (moisture, electric or magnetic fields, UV, temperature, pH or ion composition). In the performance of 4D printed devices, time is involved as the 4th dimension. 4D smart structures have been known for many years in the scientific literature, well before the advent of 3D printing, and the concepts of shape evolution as well as self-assembly have been applied to drug delivery at the nano-, micro- and macro-scale levels. The neologism “4DP” was coined by Tibbits, Massachusetts Institute of Technology, in 2013, who also showed the earliest examples of 4D printed objects. Since then, smart materials have often been combined with additive manufacturing, which makes production of complex shapes easy to achieve: going beyond 3DP, 4D printed items are no static objects. Two main categories of raw materials have been employed for 4DP: shape memory polymers (SMPs) and shape morphing hydrogels (SMHs). In principle, all types of 3D printers could be used for 4DP. In this article, examples of systems for use in the biomedical field, such as stents and scaffolds, and in drug delivery are reviewed, with special emphasis on indwelling devices for retention in the urinary bladder and in the stomach. [Display omitted]